2011
DOI: 10.1007/s10336-011-0719-9
|View full text |Cite
|
Sign up to set email alerts
|

A rapid effect of handling on counts of white blood cells in a wintering passerine bird: a more practical measure of stress?

Abstract: Measuring circulating glucocorticoids is a widely used method to assess stress in animals. However, hormones must be sampled within the first few minutes of capture, which makes it difficult to discriminate between hormone baseline levels and the levels caused by capture and handling stress. The use of white blood cell (WBC) counts made from blood smears represents an alternate method for measuring physiological stress. Since the increase in glucocorticoid hormones causes characteristic long-lasting changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 47 publications
0
50
0
11
Order By: Relevance
“…Corticosterone is the main adrenocortical hormone present in the peripheral blood. Elevated blood corticosterone levels and heterophil to lymphocyte (H/L) ratios are well-known physiological indicators of welfare (Rogers et al, 2015;Alm et al, 2016), and are used as a stress indicators in poultry (Delezie et al, 2007;Cirule et al, 2012). Corticosteroids contribute for the reestablishment of homeostasis via negative feedback mechanisms that act on the hypothalamus and/or pituitary structures, decreasing HPA axis activation (Canoine et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Corticosterone is the main adrenocortical hormone present in the peripheral blood. Elevated blood corticosterone levels and heterophil to lymphocyte (H/L) ratios are well-known physiological indicators of welfare (Rogers et al, 2015;Alm et al, 2016), and are used as a stress indicators in poultry (Delezie et al, 2007;Cirule et al, 2012). Corticosteroids contribute for the reestablishment of homeostasis via negative feedback mechanisms that act on the hypothalamus and/or pituitary structures, decreasing HPA axis activation (Canoine et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The handling time of sampled birds (including transport from walk-in traps) was less than 1 h and in most cases less than 45 min. Although it has been reported that avian heterophil or lymphocyte counts can occasionally change within 60 min of capture (Cīrule et al 2012), studies on shorebirds (Buehler et al 2008;D'Amico et al 2017) and some passerines (Davis 2005) indicated that H/L ratio is relatively stable within the first hour after capture. Consequently, we assumed that the measurements of shorebird leukocyte profiles were unlikely to be affected by handling stress under our sampling protocol.…”
Section: Leukocyte Profilesmentioning
confidence: 98%
“…Dicho volumen re presenta el 0.25% de la masa corporal del ave, considerando un promedio de masa de 11.98±0.68 g para la especie (datos de este estudio). Asimismo, el tiempo en que manipulamos al individuo capturado fue menor a los 30 min para evitar un incremento en los niveles de leucocitos (Cīrule et al 2012). En campo realizamos los frotis sanguíneos, los cuales dejamos secar a temperatura ambiente, para luego fijarlos con metanol al 100%; posteriormente, en el laboratorio los teñimos con el colorante Giemsa durante 55 min.…”
Section: Métodosunclassified